An Reading Exercises in English Language Textbook for the Eleventh Grade of Senior High School - Ade Nurul Fadillah; Sri Suci Suryawati (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
This research discussed about reading exercises in Bahasa Inggris textbook for the eleventh grade of senior high school published by the indonesian ministry of education. The objective of this research is to analyze the kinds of cognitive domain Bloom’s Taxonomy in reading exercises of Bahasa Inggris Textbook for the Eleventh Grade of Senior High School. This research was descriptive qualitative content analysis because the data were was gathered from documents which is the reading exercises that contained in Bahasa Inggris Textbook. In this research the data collection technique was documentation. There were some steps in collecting the data such as read the textbook, list and collect the considered data, and lastly provide the table to put all the considered data from the textbook. In data analysis, this research used procedures consist of data reduction, data display and conclusions drawing. The results of this research showed that the proportion of each level in Bahasa Inggris Textbook was unbalance. The highest percentage belonged to the analyzing level was 30.30% the remembering level was 19.69 %, the understandig level 18.18 %, the applying level 16.66%, and the lowest percentage belong to evaluating level were 15.15%. The distribution of lower order thinking which consisted of remembering, understanding and applying consist of 36 tests (54.54%). The distribution of higher order thinking skill which consisted of analyzing and evaluating consist 30 tests (45.45%).